More Than Teaching Values: Teacher Exemplarity and Moral Formation through the Figurative Learning Model - Moch Tohet; Faridatun Nuraini (Indonesian Journal of Education and Social Studies, 2026)
This study aims to examine the implementation of the Figurative Learning Model as an exemplar-based pedagogical approach to addressing moral challenges among adolescents at Madrasah Aliyah Negeri 1 Probolinggo, Indonesia. The research is grounded in concerns over declining moral behaviors among students, including low levels of discipline, responsibility, empathy, and politeness, despite their immersion in an Islamic educational environment. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, Islamic education teachers, guidance counselors, and students. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the Figurative Learning Model significantly enhances students’ moral awareness and behavior, particularly in terms of discipline, social empathy, responsibility, and respectful conduct. Teachers’ consistent role modeling, emotional engagement, and daily moral habituation function as powerful mechanisms for moral internalization among students. These findings align with Albert Bandura’s Social Learning Theory and Kolb’s Experiential Learning Theory, emphasizing learning through observation and lived experience. The study concludes that exemplar-based moral education constitutes an effective, contextual, and sustainable strategy for fostering adolescent character development in Islamic secondary education settings.